Polymeric microparticles for modified release of NPK in agricultural applications - Chagas, Junior Olair; Gomes, Jose Messias; Matos Cunha, Isabela Cristina de; Silva de Melo, Nathalie Ferreira; Fraceto, Leonardo Fernandes [UNESP]; Silva, Gilmare Antonia da; Lobo, Fabiana Aparecida (Elsevier B.V., 2020)
The aim of this work was to synthesize polymeric microparticles as carriers for nitrogen, phosphorus, and potassium (NPK fertilizer) for agricultural applications, using polyglycerol (PG) to improve the synthesis procedure. Multivariate experimental designs were employed to obtain a satisfactory synthesis. The desirability function identified the best conditions for preparation of the microparticles as being 100.00 mg of poly(E-caprolactone) (PCL), 825.00 mg of PG, 9.25 mL of chloroform, and 0.9% w/v of polyvinyl alcohol (PVA). This resulted in average encapsulation rates of 94.23% for N, 99.80% for P, and 65.00% for K. The profile of release from the microparticles was according to diffusion following Fick's Law. These observations confirmed the capacity of the proposed microparticles to sustain a continuous and prolonged release of NPK for the purpose of plant fertilization. (C) 2018 Production and hosting by Elsevier B.V. on behalf of King Saud University.
Keywords: Polymeric microparticles; Modified release; Fertilizers; Polyglycerol; Multivariate optimization